DEVELOPMENT OF STUDENT WORKSHEETS USING PROBLEMS BASED ON MOMENTUM AND IMPULSE MATERIALS FOR PHYSICS LEARNING IN SENIOR HIGH SCHOOL - Enjellina, Silvy (Universitas Negeri Padang, 2024)
The 2013 curriculum demands the studentsactiveness in learning and recommends one d, namely the problem-based model of learning. The aims of this study are 2, that is 1) To produce problem-based worksheets of student on momentum and impulse material forphysics learning in senior high school. 2) To reveal the quality of problem-based worksheets of student on momentum and impulse material forphysics learning in senior high school, in terms of validity and practicality.The research was conducted using the model of ADDIE development. The object of the research is a problem-based student worksheet on momentum and impulse material. The data collection instruments used test sheets of validityandtestsheets of practicality. The data analysis technique used is product validity analysis and product practicality analysis. The first studyresults, the worksheets of student produced are by the design made and have a structure based on the 2008 Ministry of National Education. The worksheets of student have a steps PBL model. The second studyresults, the feasibility of PBLworksheets of student on momentum and impulse material in terms of validity tests are in the category was very valid with the value of average on student worksheet validation from experts being 84.6%. and in terms of practicality the Physics teacher, is in the category was very practical with anvaluein average of 88.17% and the practicality test by students is in the category was very practical with an valuein average of 91.47%. So it can be concluded that the problem-based worksheets of student on Momentum and Impulse Materials that have been developed have good validity and practicality and can be used in the Physics process of learning.